Perbandingan LC50 - 72 Jam terhadap Mortalitas Ikan Cere (Gambusia Affinis) pada Limbah Sungai, Laundry, dan Oli Bengkel - Adinda, Diva; Putri, Irma Leilani Eka; Atifah, Yusni (Asian Journal of Science, Technology, Engineering, and Art, 2024)
The cere fish species (Gambusia affinis) is a small fish, which is 2-3 cm. This fish is a wild fish that fills rivers, ditches and ditches. Cere fish are generally easy to adapt and reproduce. However, the water that irrigates rivers, ditches and ditches often contains community wastes, whether in the form of household waste, laundry, or even oil waste from workshops. So this study aims to obtain the LC5o-72 hour value of waste originating from river waste, laundry, and workshop oil on cere fish mortality. This research was conducted using a completely randomized design experiment. Each waste was treated in 4 treatments with different doses, namely 5 ml/L, 10 ml/L, 25 ml/L, and 50 ml/L for 72 hours with checking every 3 hours, 24 hours, 48 hours, and 72 hours. The results showed that laundry waste had a tolerance limit at a concentration of 10 ml/L and waste oil at a concentration of 25 ml/L.